Pelatihan dan Pendampingan Penyusunan Laporan Keuangan Digital bagi UMKM Kampung Batik Cibuluh Menggunakan Aplikasi Siapik - Nugroho, Herbirowo; Hafiduddin; Sixpria, Nedsal; Ramadhani, Annisa Alifa (Institut Pesantren Sunan Drajat Lamongan, Indonesia, 2025)
Information system technology can provide convenience in all sectors including the business sector. One of these information system technologies is an accounting information system that can facilitate a company including SMEs, in presenting reliable, effective, efficient and easy information to manage business operational activities. However, there are still many SMEs, especially in Bogor, who still record transactions traditionally, manually and have not made financial reports that are in accordance with standards. The solution to this problem is to give an accounting literacy improvement program for SMEs, in this case SMEs in Kampung Batik Cibuluh Bogor through the PPIBM D3 Accounting PNJ which is carried out by holding training and mentoring in recording accounting and reporting business finances using the digital financial recording application named SIAPIK. The purpose of this training is to improve the knowledge and skills of SMEs in Kampung Batik Cibuluh, Bogor in doing bookkeeping and preparing higher quality financial reports so that they can be used for various purposes such as submitting additional capital to banking institutions for business development. The training is carried out using tutorial methods, case studies/simulations and practice. The target achievement of this training activity is expected so that UMKM actors in Kampung Batik Cibuluh, Bogor can do bookkeeping and prepare financial reports according to SMEs standards correctly and independently by using digital-based accounting applications. The results of this training activity have a significant impact on MSMEs in carrying out financial recording activities through the SIAPIK application